ΜΕ ΑΦΟΡΜΗ ΤΗΝ ΗΛΕΚΤΡΟΝΙΚΗ ΚΑΤΑΓΡΑΦΗ ΤΩΝ ΠΡΕΣΒΕΙΩΝ ΤΗΣ ΒΕΝΕΤΟΚΡΑΤΟΥΜΕΝΗΣ ΚΡΗΤΗΣ (130Σ-150Σ ΑΙΩΝΑΣ): ΜΙΑ ΠΡΩΤΗ ΠΡΟΣΕΓΓΙΣΗ ΤΟΥ ΑΡΧΕΙΑΚΟΥ ΥΛΙΚΟΥ - ΚΟΥΜΑΝΟΥΔΗ ΜΑΡΙΝΑ (Eoa kai Esperia, 2007)
Embassies were the main channel of communication between thepopulation of Venetian dominated Greek territories and the mother city.According to Venetian legislation the right to send embassies to Venice wasreserved for corporate bodies. This article presents the initial results of thecomputerization of published and unpublished texts of Cretan embassiesthrough a database system and examines their significance as primary sourcesfor the study of the history of Crete and especially the communal institutionsduring the decisive first three centuries of Venetian rule.